Productive performance and carcass traits of Nellore x Aberdeen Angus and Nellore x Red Angus heifers under tropical conditions - Andrade Moreira, Paulo Sergio; Lourenco, Fabio Jose; Neto, Angelo Polizel; Martins, Lilian Rigatto; Jorge, Andre Mendes [UNESP]; Machado Neto, Otavio Rodrigues [UNESP] (Univ Antioquia, Fac Ciencias Agrarias, 2015)
Background: Angus breed strains (Black and Red) perform differently under tropical conditions. Objective: to evaluate differences among F1 Nellore x Aberdeen Angus and F1 Nellore x Red Angus regarding productive performance and carcass traits under tropical conditions. Methods: forty-one heifers were used to assess the effect of both genetic groups on productive performance and carcass traits. The performance parameters evaluated were final live body weight and average daily gain. The carcass traits were: 1) hot and cold carcass weight and cold carcass dressing percentage, 2) carcass conformation and fatting (both ranging from 1 to 5), 3) back fat thickness, 4) rib eye area, 5) cutability, and 6) total usable meat, and commercial cut yield. Animals were divided in two groups and fed Megathyrsus maximum grass in three pens for 28 days. After this period, animals were relocated in a feedlot system for 84 days, and weighed at the beginning and at the end. All data were subjected to analysis of variance with initial live weight as a covariate. Results: differences were found between groups for productive performance and carcass traits such as back fat, and rib eye area. However, no difference was observed for conformation, fatting, ease of cutability, total usable meat, and Brazilian commercial cuts. Conclusion: F1 Nellore x Aberdeen Angus heifers had increased growth performance and carcass traits under tropical conditions.
Keywords: growth; hair coat; precocity; tropic; ultraviolet radiation; weight gain